Játékelmélet és jog; Game theory and law - Kóczy Á. László (Hungarian Academy of Sciences, Institute of Economics, 2019)
– Game theory is the pocket knife of conflict modelling: it has tools, models for practically all strategic conflicts, be that two- or multiplayer, complete or incomplete information and so on. In this study we have collected relevant tools for young lawyers. Since this is an introductory text we have avoided mathematical formalism, but offered guidance for further reading especially regarding the academic literature in Hungarian.
Keywords: C70; K00; 330; game theory; law; applications